PERSEPSI GURU TENTANG PELAKSANAAN KEPALA SEKOLAH YANG EFEKTIF DI SEKOLAH DASAR NEGERI KECAMATAN LAREH SAGO HALABAN KABUPATEN LIMA PULUH KOTA - Silvi Dalevia (Universitas Negeri Padang, 2013)
The goal of this research are to see information about implementation of effective headmaster school task. The population is 208 teachers and the sample is 108 people that taken by stratified proportional random sampling. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using by comparing the average scores by an average score multiplied by 100% ideal. The result of this research are the perception of teacher to concern about implementation of effective headmaster school task in SD negeri Kecamatan Lareh Sago Halaban Kabupaten Lima Puluh Kota stay in Effective category. Kata kunci: Effective Headmaster School